2021
DOI: 10.1177/10600280211055804
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucagon-Like Peptide-1 Receptor Agonists (GLP-1RA) on Food Content During Esophagogastroduodenoscopy (EGD)

Abstract: Background Glucagon-like peptide-1 receptor agonists (GLP-1RA) have delayed gastric emptying properties; however, the impact on esophagogastroduodenoscopy (EGD) visualization is unknown. Objective: This study examines the impact of GLP-1RA use on EGD visualization and gastric content retention. Methods: This was a retrospective cohort study with matched controls. The primary endpoint was the odds of retained food documented during EGD. Secondary endpoints included incidence of lavage and need for repeat EGD du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
(11 reference statements)
1
24
0
2
Order By: Relevance
“…Of note, a large retrospective study (n = 85,116) observed that only 3% of EGD patients had RGV. 7 In this study, the use of a GLP-1RA (6/85,116 patients) was not associated with increased residual gastric content. 10 These authors concluded that RGV encountered during EGD should only be used as a surrogate for delayed gastric emptying.…”
Section: Glp-1ra-related Fasting Residual Gastric Volume Several Stud...mentioning
confidence: 48%
See 2 more Smart Citations
“…Of note, a large retrospective study (n = 85,116) observed that only 3% of EGD patients had RGV. 7 In this study, the use of a GLP-1RA (6/85,116 patients) was not associated with increased residual gastric content. 10 These authors concluded that RGV encountered during EGD should only be used as a surrogate for delayed gastric emptying.…”
Section: Glp-1ra-related Fasting Residual Gastric Volume Several Stud...mentioning
confidence: 48%
“…A retrospective cohort study of patients taking GLP-1RA (n = 59) with matched controls (n = 118) reported RGV in 6.8% (4 of 59) patients taking GLP-1RA versus 1.7% (2 of 118) in the control group. 7 Another case-control study observed an overall 1.5% (17 of 1128) incidence of RGV in unmatched patients undergoing EGD. 8 With propensity score matching (n = 205 pairs) these authors reported that even after ≥12 hours of fasting, RGV was 5.4% in patients taking a GLP-1RA compared with 0.5% controls.…”
Section: Glp-1ra-related Fasting Residual Gastric Volumementioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, a recent retrospective cohort study comparing 59 patients on GLP-1 agonist therapy to 118 matched controls assessing for retained gastric food on EGD failed to reach a statistically significant difference; although, this study may have benefitted from a larger sample size. 15 In conclusion, the risk of perioperative aspiration with patients on GLP-1 therapy is not clear. However, as both our patients had large volumes of particulate gastric contents, a cautious approach is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent retrospective cohort study comparing 59 patients on GLP-1 agonist therapy to 118 matched controls assessing for retained gastric food on EGD failed to reach a statistically significant difference; although, this study may have benefitted from a larger sample size. 15…”
Section: Discussionmentioning
confidence: 99%